Role of Foetal Trans-cerebellar Diameter in the Prediction of Gestational Age in Correlation with other Foetal Biometric Parameter: A Cross-sectional Study in a Secondary Hospital of Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: Uncertain gestational age is associated with higher perinatal mortality rates. Accurate assessment of gestational age is an important parameter in obstetrics for the management of pregnancy and evaluation of foetal development.Objective: To evaluate whether trans-cerebellar diameter (TCD) in singleton uncomplicated gestations can serve as a reliable predictor of gestational age (GA) in fetuses between 18-38 weeks of pregnancy.Methods: This cross-sectional study was carried out in the department of Radiology and Imaging of CMH, Ghatail, from January 2019 to December 2019 among purposively selected 89 outpatient and admitted pregnant women without any complication having regular menstrual cycle and confirmed about last menstrual period (LMP). The transabdominal USG was performed in each patient and trans-cerebellar diameter was taken which was later correlated with other foetal biometric parameters like biparietaldiameter (BPD), femoral length (FL) etc.Results: Most of the patients belonged to 21-25 years age group (32.6%). Mean age of the study subjects was 26.94±5.70 years ranging from 19 to 38 years and were predominantly (51.7%) primipara. Mean gestational age was 220.69±37.30 days by LMP, 216.20±36.06 days by BPD, 219.00±38.43 days by FL and 218.81±39.36 days by TCD. Mean of biparietal diameter, femoral length and transverse cerebellar diameter were 7.59±1.40cm, 5.91± 1.33cm and 3.93±1.00cm respectively. A significant positive linear correlation between GA by LMP with GA by BPD, FL and TCD was observed (p